EVALUATION OF ENVIRONMENTAL SITUATION IN NARTA LAGOON, VLORA, ALBANIA : Received: 07th March 2022; Revised: 09th April 2022, 14th June 2022, 24th June 2022; Accepted: 25th June 2022 - Bakaj, Aurora; Kiçaj, Hajdar; Ismailaj, Mariola; Arapaj, Xhuljana; Mehmeti, Sibora (MATTER: International Journal of Science and Technology, 2022)
Narta Lagoon is one of the biggest Lagoons in Albania. It is situated in the southern part of the Vjosa River delta. Two canals in the northwest and southwest parts of the lagoon connect it to the Adriatic Sea. These artificial canals enable the water exchange process with the sea during tidal flow. Vjose - Narta area is considered a Protected Landscape, so environmental monitoring is important. Setting and design: Water samples were taken monthly, at six evenly distributed sample stations. The study was conducted from January – to December 2018. Materials and methods: The assessment of microbial contamination was performed with the MPN method. Total coliform, fecal coliform, and fecal streptococci were tested as fecal contamination indicators. PH and salinity were the physicochemical parameters analyzed. Conclusions: the cleanest sampling station is the one near contact with the seawater. The most polluted stations are stations 2, 4, and 6. Temperature values range from 5 oC in January to 33 oC in August. Lagoon pollution is caused by an anthropogenic factor as well as a lack of appropriate cleaning strategies.